Preservices creative thinking skills on biotechneur programs. Issue 2 (February 2019) - Natadiwijaya, I F; Rahmat, A; Redjeki, S; Anggraeni, S
Abstract: The aim of this research is to know how the biotechneur program influences towards creative thinking skills of biology preservices teacher. The lessons were held for 14 lectures, divided into four phases. Each phase contains learning strategies that support the formation of students' creative thinking skills. The subjects in this study is 34 biology preservices teacher who take biotechnology courses at the University of Wiralodra. The instrument used in this research is 5 essay test items of creative thinking skill in biotechnology. The answers are then given a score using assessment guidelines rubric to obtain data in the form of a score at the time before and after learning. The data is then analyzed quantitatively with the result n-gain value in the medium category and in a significant decision. Based on the results of data analysis it can be concluded that the biotechneur program influences towards creative thinking skills of biology preservices teacher, with all the creative thinking aspects has been developed very well. This research has also revealed that biotechnology programs can be combined with entrepreneurship, and not just an enhanced creative thinking skill but also produce biotechnology products that made from local resources and have high economic value.